Identification of chimeric RNAs in human infant brains and their implications in neural differentiation. (June 2019) - Tang, Yue; Ma, Shanshan; Wang, Xinxin; Xing, Qu; Huang, Tuanjie; Liu, Hongtao; Li, Qinghua; Zhang, Yanting; Zhang, Kun; Yao, Minghao; Yang, Greta Luyuan; Li, Hui; et al.
Abstract: Chimeric RNAs are transcripts composed of RNA fragments from different genes and are traditionally well-known cancer-causing genetic events. Recent studies show chimeric RNAs being present in multiple non-neoplastic tissues and cells, suggesting that at least some may have roles in normal physiology. However, chimeric RNAs and their implications in brain development and neural differentiation have not been formally studied. Here, we firstly characterized the landscape of chimeric RNAs in human infant brain tissues and identified 599 chimeric RNAs. Through a series of filtering, 22 were selected and tested in a neural differentiation process starting from stem cells. Ten were validated experimentally. One of these ten chimeric RNAs, DUS4L-BCAP29, dramatically increased when human umbilical mesenchymal stem cells were induced for neural differentiation. Consistently, we found that overexpressed DUS4L-BCAP29 effectively promoted neural differentiation. Our results support the important role(s) chimeric RNAs play in neural differentiation, and are consistent with the new notion that chimeric RNAs also exist in normal physiology, and likely serve biological purposes.